Efficacy of 3D slicer-assisted minimally invasive thrombolysis combined with soft channel drainage versus craniotomy: a retrospective study in moderate basal ganglia hemorrhage - Chen, Huaxuan; Tang, Hui; Shang, Bin; Luo, Bo; Qiao, Fei; He, Qiuguo; Li, Pengcheng (Frontiers in Neurology, 2025)
BackgroundThe optimal clinical treatment strategy for moderate basal ganglia hemorrhage (30–50 mL) remains a subject of debate. This study aims to evaluate the clinical efficacy of 3D Slicer-assisted minimally invasive thrombolysis combined with soft channel drainage by comparing it with traditional craniotomy, thus assessing the clinical value of this minimally invasive approach.MethodsIn this retrospective study, the patients were divided into the minimally invasive group and the craniotomy group based on surgical approaches. The study compared operative time, hematoma clearance rates, and postoperative complication rates between the two groups. Functional recovery was assessed at 6 months postoperatively using the modified Rankin Scale (mRS) and Barthel Index. Additionally, the study analyzed differences in medical costs and cost-effectiveness between the two treatment approaches.ResultsA total of 112 patients were enrolled, with 41 in the minimally invasive group and 71 in the craniotomy group. Baseline characteristics showed no significant differences between groups (all p > 0.05), including demographics [e.g., sex: 30 males (73.2%) and 11 females (26.8%) vs. 51 males (71.8%) and 20 females (28.2%)], median age: [70 (63.5–76.5) years vs. 65 (58–72) years], median hematoma volume: [40.6 (37.7–47.8) mL vs. 41.2 (35.4–45.1) mL], median GCS score: [9 (8–11) vs. 10 (9–11)], median NIHSS score: [15 (11.5–18) vs. 12 (10–18)], median midline shift [3.70 (2.85–5.10) mm vs. 4.20 (3.20–5.70) mm], and proportion of intraventricular hemorrhage [6 (14.6%) vs. 14 (19.7%)]. Hematoma location and underlying diseases were also comparable. Compared to the craniotomy group, the minimally invasive group exhibited significantly less intraoperative blood loss, shorter operative time, lower rates of tracheostomy and pulmonary infection (p < 0.05), and smaller volume of cerebral edema at 72 h postoperatively (p < 0.05). Follow-up results 6 months postoperatively indicated that the minimally invasive group had significantly lower mRS scores and higher Barthel Index scores (p < 0.05). Regarding healthcare costs, expenses were lower in the minimally invasive group, and the incremental cost-effectiveness ratio (ICER) was more favorable (p < 0.05).Conclusion3D Slicer-assisted minimally invasive thrombolysis combined with soft channel drainage represents an effective treatment for patients with moderate basal ganglia hemorrhage. It offers several advantages, including precise localization, minimal surgical trauma, a low complication rate, favorable safety profile, and cost-effectiveness. Therefore, this minimally invasive technique holds significant clinical value.